2016
DOI: 10.1167/16.5.16
|View full text |Cite
|
Sign up to set email alerts
|

Gradients of relative disparity underlie the perceived slant of stereoscopic surfaces

Abstract: Perceived stereoscopic slant around a vertical axis is strongly underestimated for isolated surfaces, suggesting that neither uniocular image compression nor linear gradients of absolute disparity are very effective cues. However, slant increases to a level close to geometric prediction if gradients of relative disparity are introduced, for example by placing flanking frontal-parallel surfaces at the horizontal boundaries of the slanted surface. Here we examine the mechanisms underlying this slant enhancement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 51 publications
(96 reference statements)
1
12
0
Order By: Relevance
“…This is evident in an increase in apparent slant [40, 4247] and a decrease in the time taken for it to be seen [4042, 48]. This increase in apparent depth results from gradients of relative disparity provided by both the outline of the surface, and its texture [49]. …”
Section: Introductionmentioning
confidence: 99%
“…This is evident in an increase in apparent slant [40, 4247] and a decrease in the time taken for it to be seen [4042, 48]. This increase in apparent depth results from gradients of relative disparity provided by both the outline of the surface, and its texture [49]. …”
Section: Introductionmentioning
confidence: 99%
“…The fixation cross was not visible during stimulus presentation, leaving only the flanking lines as a fixation aid and cue to the depth of the screen plane. This minimal fixation aid ensured that participants could not make judgments using relative disparity information between the stimulus edges and any surrounding fixation stimulus (e.g., Wardle & Gillam, 2016).…”
Section: Stimulimentioning
confidence: 99%
“…Previous research on surface discontinuities has shown contradictory effects. In some cases, the presence of discontinuous edges can enhance perceived depth compared to continuous disparity changes (Cammack & Harris, 2016;Deas & Wilcox, 2014, 2015, and can improve slant discrimination thresholds (Wardle & Gillam, 2016). Conversely, some discontinuous surface arrangements lead to reductions in perceived depth, as in the depth variant of the Craik-O'Brien-Cornsweet illusion (Anstis, Howard, & Rogers, 1978;Rogers & Graham, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Beginning at V2, and continuing through multiple cortical sites, neurons show selectivity for relative disparities, that is, for differences between absolute disparity measurements across space (Fang et al, 2018;Neri, Bridge & Heeger, 2004;Thomas, Cumming & Parker, 2002;Umeda, Tanabe & Fujita, 2007). Although sensitivity for relative disparities has not been modeled extensively (cf., Assee & Qian 2007;Zhaoping, 2002), numerous psychophysical observations suggest the importance of processes operating at this level (e.g., Deas & Wilcox, 2014;Deas & Wilcox, 2015;Glennerster & McKee, 1999;Glennerster & McKee, 2004;Goutcher & Hibbard, 2010;Goutcher, Connolly & Hibbard, 2018;Goutcher & Wilcox, 2016;Vreven, McKee & Verghese, 2002;Wardle & Gillam 2016). Such results indicate that the tuning properties of relative disparity mechanisms are critically important for understanding the perception of cyclopean form (Goutcher et al, 2018;Hibbard, 2005;Tyler, 1975;Tyler, 2012;Tyler & Kontsevich, 2001).…”
Section: Introductionmentioning
confidence: 98%
“…Cyclopean perception (Julesz, 1971), our ability to perceive the 3D shape and structure of surfaces from binocular disparity alone, may, for example, be limited primarily by early absolute disparity measurement processes, as noted earlier. Alternatively, performance impairments may be more directly related to limitations in the measurement of relative disparities, or in the use of these measurements for the description of cyclopean form (e.g., Goutcher & Wilcox, 2016;Goutcher et al, 2018;Wardle & Gillam, 2016). In this article, we report the results of experiments measuring performance impairments for cyclopean surface perception in the presence of different forms of random-dot masking stimuli.…”
Section: Introductionmentioning
confidence: 99%